The Relative Financial Cost and Benefit of an Ophthalmology Resident Compared to an Advanced Practice Provider, Optometrist, or Faculty Ophthalmologist - Moore, Daniel B.; Barr, William (Journal of Academic Ophthalmology, 2018)
Objective The main objective of the article is to determine the relative direct financial cost and benefit of an advanced practice provider (APP), optometrist, and faculty ophthalmologist compared with an ophthalmology resident.Design Single center cost–benefit financial analysis.Methods The direct total expenses, including mean salary and benefits; the cost/week, based upon calculated hours worked; and net revenue, based upon technical collections subtracted from total expenses were collected for all APPs, optometrists, faculty ophthalmologists, and ophthalmology residents at the University of Kentucky for the 2016 to 2017 academic year. Optometry and ophthalmology faculty collections were adjusted for clinical full-time equivalents.Results Total annual mean salary and benefits for 242 APPs, 4 optometrists, 17 faculty ophthalmologists, and 9 ophthalmology residents were $126,797, $117,021, $338,233, and $71,210, respectively. Assuming a 50-hour-work week, the calculated hourly costs were $48.77, $45.01, $130.09, and $27.39, respectively. Ophthalmology residents do not directly generate work relative value units or collections. On this basis, the net annual revenues were −$62,729, $122,757, $566,119, and −$71,210, respectively.Conclusions Ophthalmology residents are relatively inexpensive compared with potential substitute health care providers, although they are unable to generate direct revenue. Indirect costs and benefits are likely substantial, but currently incalculable. More candid analyses of the role and financial impact of trainees in health care are needed.
Keywords: resident education; cost of training; housestaff; cost of education